Efektivitas Cyhalofop-butyl Mengendalikan Gulma pada Budidaya Padi Sawah Tabela - Uum Umiyati; Denny Kurniadie; Deden Deden (Agrotechnology Research Journal, 2021)
High competition in the early growth phase will suppress growth and reduce rice yields. Presence of weeds in the rice field ecosystem needs to be controlled. Weed control with herbicides is more effective than other controls. This study aims to determine the effectiveness of the herbicide Cyhalofop-butyl in controlling weeds in the cultivation of direct seeds rice cultivation. The research was conducted in Sekaran village, Wonosari sub-district, Klaten district, Central Java. The method used was randomized block with seven treatments and four replications. The treatment consisted of a dose of the herbicide Cyhalofop-butyl 100 g.L-1 with levels: (50, 75, 100, 125, 150, and 175 L.ha-1), mechanical weeding and control (no weeding). The results showed that Cyhalofop-butyl at a dose of 50–175 L.ha-1 was effective in controlling the weeds of Echinochloa crus-galli, Leptochloa chinensis and other weeds at 3 weeks after application up to 6 weeks after application, without causing phytotoxicity effect on rice plants, herbicide Cyhalofop-butyl does not affect the growth and production of rice but reduces competition between weeds and rice plans. Herbicide Cyhalofop-butyl applied at a dose of 50 - 175 L.ha-1 provide rice grain yield of 10,25 - 11,50 kg per plot.